Physiotherapeutic treatment for articular instability in ankle sprains - Vieira, Sandro Emílio (2020)
The prevalence of ankle sprains in non-athletes, amateur and professional athletes is high, being specifically a very common disorder of the musculoskeletal system in the lower limbs according to the studies cited at work. Ankle sprain is often an injury caused by trauma in excessive inversion of the foot, which can be classified through this injury mechanism. With a high prevalence of persistent joint instability, ankle sprains have recurrent trauma in several cases, thus justifying the chronicity of the condition. The aim of the study was to establish the relationship between ankle sprain and the developed joint instability and physical therapy treatment in athletes and non-athletes with this type of injury. The methodological resource of the work was a bibliographic review of the injury and the physiotherapeutic conduct, where relevant articles and books were selected, correlating the prevalence of ankle sprains and joint instability, proposing the physiotherapeutic treatment and the general picture of the sprains is not aimed at here. ankle, but in articular instability. The conclusion of the study confirmed the high prevalence of chronic joint instability in ankle sprains and physiotherapeutic treatment based on muscle strengthening and proprioceptive training was also shown to be an effective approach for this clinical condition.